LANGUAGE DEVIATION: BRINGING LANGUAGE FROM SCIENCE TO FASHION - Nisa Roiyasa; Muhamad Ahsanu; Binta Nurul Azkiya (Program Studi Pendidikan Bahasa Inggris Fakultas ilmu Budaya, 2021)
The article argues that the non-literal way of thinking is the potential force in creating language creativity in lives. Besides to be brought as a means of communication, language should be delivered in a more personal and mediating for every student’s individual character, voice, culture, and background. The direction of ELT is still to the conformity to situational communicative functions. Class is considered as a place for equipping students with situational-linguistic features so they are able to fulfill the communicative demands in some particular situations (science). Language deviation can be introduced to the class for the students to be able to cloth free and personal feeling, thoughts, and aspirations (fashion). The study applied library-study approach to answer the inquiries. It suggests that Language deviation requires the user to have prior knowledge in English and to have higher level of creativity. Students can learn to play with the language by applying foregrounding. Foregrounding involves stylistic distortion of a certain language at any level of language. In classrooms, teachers can apply lexical distortion in the form of neologism and semantic distortion to challenge students to be able to think beyond literal meaning.